Accountability as a practice: a case study of a nongovernmental development programme in Tanzania. Issue 5 (4th July 2022) - Berghmans, Mieke
ABSTRACT: The number of empirical studies focusing on NGO accountability practices remains limited. This paper responds to this gap. It presents the accountability practices identified in an empirical study of a nongovernmental development programme in Tanzania. Drawing on data collected through field work and analysed through coding, visualisations, and detailed descriptions, this study observed how practices constituting this development programme were held together by accountability practices. This paper analyses these accountability practices: (a) prescribing–reporting–verifying, (b) measuring, (c) contracting, and (d) capacity building, learning, and acting together. It demonstrates how these accountability practices facilitate the coordination of this development programme.